(3GdLed(B- (3aj GdfMhs - (3GdRLGLj , CHh GdbGSe,J (B337 (3g` s ((3SdGeI Hf HhSjO Hf SdGeI GdefLGH s)
(3ChdgG (B:s
(3CbSGe GdcdGe KdGKI(B: (3GSe haYd hMQa LGA deYfi aGdGSe eG LGR Cf jchf aGYdkG Ch eaYhdkG s
(3BNQgG (B:s
(3aeG SHb GdbjSj ef ShA SjQI hdcf WaJ YdeGA oYRdI NGdO jQjO Ydi GdeGA aGage gPG hJOHQ LejYg JQTO ced GdcJGH s
(3fSNI NGeSI JJab aj ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa aj HYV GdCdaGXs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B299 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B124s
Keywords: (3GdfMhs